Model of Theocentric-Humanistic Character Education Development in Islamic Educational Establishments - Ali Hasan Siswanto; Mukaffan Mukaffan (STAI Syaichona Moh. Cholil Bangkalan, 2024)
This article describes the Theocentric-Humanistic Character Education Development Model at the Miftahul Jannah Islamic Boarding School in Lumajang Regency. This study uses a qualitative approach with a descriptive method through a case study approach—data analysis from interviews, observations, and documentation with stages of reduction, display, and verification. The theocentric humanistic character education development model implemented at the Miftahul Jannah Islamic Boarding School has three important development models, namely: a) formulating theocentric-humanistic character competencies in the curriculum, b) applying inclusive learning methods, c) scheduling habituation activities in religious activities.